Teknologi Pembuatan Kompos pada Kelompok Tani Sumber Bibit untuk Pengelolaan Limbah Organik dan Peningkatan Kesuburan Tanah - Badaruddin, Rusli; Saili, Takdir; Asminaya, Nur Santy; Bahtiar, Bahtiar; Hakim, Muh. Haidir; Putri, Anindyaningrum Zainal; Hadini, Hairil Adzuliyatno; Sandiah, Natsir (Mestaka: Jurnal Pengabdian Kepada Masyarakat, 2025)
The community service program focused on the Sumber Bibit Farmers Group, located in Mokoau Village, Kambu District, as the implementation site. The program aimed to enhance farmers’ knowledge and skills in processing organic waste into compost fertilizer that benefits soil fertility. The main challenge faced by the farmers’ group was the accumulation of waste derived from living organisms, both from agricultural activities and household waste, which had not been optimally utilized. The activity was carried out through training, demonstrations, and hands-on guidance in processing organic waste using simple technology with the help of local microorganisms (MOL) as bioactivators. Participants were involved in every stage of the process—from material collection and fermentation to packaging the finished compost product. The evaluation results indicated an increase in participants’ understanding of the importance of organic waste management and their ability to produce and utilize compost fertilizer independently. Through this training, the farmers’ group is expected to apply the technology sustainably to support organic and environmentally friendly agriculture in the Mokoau area.